PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI VOLUME BANGUN RUANG SISI LENGKUNG DI SMP NEGERI 8 KOTA BOGOR - Suharya Suharya (Universitas Pakuan, 2021)
IMPROVING STUDENT LEARNING OUTCOMES USING THE DISCOVERY LEARNING MODEL ON VOLUME BUILDING MATERIALS ON CURVED SIDES IN JUNIOR HIGH SCHOOL (SMP NEGERI 8 KOTA BOGOR)This study departs from the phenomenon that occurs in the classroom that the low understanding and learning outcomes of students in Mathematics learning Basic Competence Determines the Volume of Curved Side Space. Therefore, a teacher needs to consider learning strategies so that they can improve student learning outcomes. The research was carried out in grades IX-A of junior high school and aimed (1) to determine the use of the Discovery Learning model in improving student learning outcomes in Mathematics. (2) To describe the process of improving student learning outcomes in Mathematics. (3) To measure the magnitude of the increase in student learning outcomes in Mathematics subjects with the Discovery Learning model. The results of this study indicate that the application of the Discovery Learning model can be a fun variation of learning for students, proven to improve student learning outcomes. There was an increase after the application of the Discovery Learning learning model to 75 in cycle 1 and 80 in cycle 2. The application of the Discovery Learning learning model can create a pleasant learning situation so that there is an increase in student learning outcomes. The application of the Discovery Learning learning model can be socialized and used as an alternative in learning Mathematics in schools within the Bogor City Education Office.